2009
DOI: 10.1007/978-3-642-02704-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Using Reinforcement Learning for Multi-policy Optimization in Decentralized Autonomic Systems – An Experimental Evaluation

Abstract: Abstract. Large-scale autonomic systems are required to self-optimize with respect to high-level policies, that can differ in terms of their priority, as well as their spatial and temporal scope. Decentralized multiagent systems represent one approach to implementing the required selfoptimization capabilities. However, the presence of multiple heterogeneous policies leads to heterogeneity of the agents that implement them. In this paper we evaluate the use of Reinforcement Learning techniques to support the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Dependency between policies has been confirmed in our previous work with non-collaborative agents [10]. We observed that implementing a single policy that only addresses emergency vehicles creates a backlog of other vehicles in the system, which in turn prevent emergency vehicles from proceeding.…”
Section: Policy Dependencysupporting
confidence: 50%
See 3 more Smart Citations
“…Dependency between policies has been confirmed in our previous work with non-collaborative agents [10]. We observed that implementing a single policy that only addresses emergency vehicles creates a backlog of other vehicles in the system, which in turn prevent emergency vehicles from proceeding.…”
Section: Policy Dependencysupporting
confidence: 50%
“…From our previous experiments [10] we have observed that policy deployments can benefit from combining policies using W-learning independently at each agent. We have also observed a high dependency between policy deployments.…”
Section: Distributed W-learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Decentralized solutions were popular in automated traffic control [284], e-Commerce [264], water networks [88], service oriented systems [47], and load balancing solutions [16]. Learning was a prominent theme for automotive [89], traffic management control [90], and e-Commerce [132]. The ability for a system to adapt its adaptation logic was a strong area of focus for mobile systems [300], ISR [254], e-Commerce [9], software engineering applications [8], [106], and systems on chip [29].…”
Section: -2010 -Ramping Upmentioning
confidence: 99%